Language Multiculturalism: Identical Words, Different Meanings of Javanese Vocabularies in Semarangan and Suroboyoan Dialects - Perangin-angin, Alemina Br.; Mulyyan, Endang; Arandha, Maria Regista (Tradition and Modernity of Humanity, 2023)
This study examines cultural attitudes, misunderstandings, communication styles, and oral and written communication between Semarang and Surabaya. This study was descriptive qualitative. The results showed that Semarang and Surabaya use Javanese, although their knowledge and language perception varied. This study uses qualitative methodologies. It uses primary and secondary data. Preliminary data was collected from Semarang and Surabaya sources. Then, journals and publications compare Semarang and Surabaya terms—every civilization's language changes. Languages change vocabulary, pronunciation, grammar, and meaning. Locals and residents speak diverse dialects. Dialect diversity creates regional vocabulary. One's function will have several formal activities. Depending on the situation, everyone has many valuable parts. Indonesia is diverse. Regional languages highlight culture and features with their dialects and individuality. Most Indonesian users are Javanese. Dialects have distinct traits. One perception background case differs. Semarang and Surabaya, both Javanese, are in different provinces. Semarang in Central Java and Surabaya in East Java have words with similar but different meanings (homophones).